PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) DENGAN MENGGUNAKAN LOOSE PARTS UNTUK MENINGKATKAN KREATIVITAS DAN KEMAMPUAN MOTORIK HALUS - Kustila (UNIB Press, 2023)
The purpose of this study was to describe the implementation of Project Based Learning (PjBL) using Loose Parts to improve creativity and fine motor skills in group B of Smart Children's Kindergarten, Rejang Lebong district, the research method used was Classroom Action Research Method (CAR) which was carried out in 3 cycles. and continued with Quasi Experiments. The subjects of this study were group B1 children who found 15 children, while the experimental sample group B1 TKIT Smart Children collected 15 children and group B2 as the control group collected 15 children. Data collection techniques using observation sheets while data analysis using t tests, based on research results can be obtained: (1) the application of the Project Based Learning (PjBL) model by using the loose part can increase creativity. (2) the application of the Project Based Learning (PjBL) model by using loose parts can improve fine motor skills. (3) the implementation of the Project Based Learning (PjBL) model by using loose parts is more effective when compared to the learning that has been done so far.